Efforts To Increase The Role Of Posyandu cadres in Achievement Of Exclusive Breast Milk Status 1 - Umami, Riza; Sutrisno, Sutrisno; Bachri, Syaiful (Jurnal Pendidikan Kesehatan, 2022)
Posyandu plays a role in suppressing MMR or IMR through data collection activities, being a health communicator, making approaches and persuasion, conducting visitations and being a liaison as well as conducting monitoring and evaluation. There are obstacles experienced by cadres in carrying out community development activities in terms of the level of education that is still lacking and has not received training on the duties of cadres in Posyandu. The purpose of this study was to analyze differences in the level of knowledge of posyandu cadres in achieving E1 exclusive breastfeeding status. The research method used is an experiment with a quasi experimental approach. The research design chosen was one group pretest-posttest design. Respondents were posyandu cadres in the Mangli Health Center area as many as 30 people. This research was carried out through several activities, namely Focus Group Discussion, training and mentoring of skill demonstrations on respondents where the activities began with a pre test and ended with a post test. The result of calculating the t test is that there are differences in the level of knowledge and demonstration of skills before and after training (0.00 more than 0.05). The success of Posyandu management certainly requires strong support from various parties, including moral, material and financial support. In addition, it is necessary to have the cooperation and dedication of the managers, including Cadres. If this Posyandu activity is well organized, it will have a major impact on reducing Maternal and Child Mortality Rates as well as reducing stunting rates.